A brazilian ergonomic human-robot interface case - Matias, Nelson Tavares; Rosado, Victor Orlando Gamarra [UNESP]; Barros, José Glenio Medeiros de; Araújo Júnior, Antonio Henriques de; Ribeiro, Rosinei Batista (Trans Tech Publications, 2013)
Brazilian and foreign companies operating in Brazil in the last 30 years have been using automated productive resources, especially robots. These 3 decades doesńt seem to have been enough to develop in the actors involved with robots an adequate professional awareness. If we consider the predictive security and ergonomic aspects involved, we notice that there are critical failures on handling these situations. So in this study we tried to observe the presence of the human being in some workstations that operate with robots in the Brazilian Southeastern region. © (2013) Trans Tech Publications, Switzerland.
Keywords: Automation; Ergonomy; Robotics; Critical failures; Foreign companies; Human being; Human-Robot Interface; Manufacture; Robots; Ergonomics